(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The exponential increase in information, primarily due to the electronic capture of data and its storage in vast data warehouses, has created a demand for analyzing the large amount of data generated by today’s organizations so that enterprise can survive in the times of recession. There are Knowledge Management is expensive. Effective management of knowledge requires hybrid solutions of people and technology. Knowledge Management is highly political. Knowledge Management requires knowledge various tools that can be used to capture and codify knowledge, include databases, data mining techniques, groupware and various types of artificial intelligence tools like expert systems. The paper outlines these techniques, and focuses on expert systems as a tool for deriving knowledge from organizations data assets.